Long-term effects of deep institutional shocks: Historical evidence from Mexico - Shai Dothan; Mitja Kovac; Rok Spruk (Journal of Government and Economics)
This paper examines the potential impact of institutional shocks on long-term development of property rights and on institutions regulating contracting. The paper seeks to demonstrate that the external institutional shocks might have an uncontemplated side-effect on the institutional development of Mexico. The analysis exploits the within-country variation in the presence of US administrative authorities during the Mexican-American conflict across Mexican states and cities. Using propensity score and nearest neighbour matching technique, we present some evidence of the potential long-term institutional implications of the presence of US administrative authorities. We show that the presence of US administrative authority generated an unexpected positive effect which could influence long-term property rights and contracting institutions of Mexican states. The positive impact of US administrative authorities’ presence are robust to a variety of specification checks and are particularly large for smaller cities.